HADHA Regulates Respiratory Complex Assembly and Couples FAO and OXPHOS - Chaoying Qin; Shasha Gong; Ting Liang; Zhenbo Zhang; Jessie Thomas; Janice Deng; Yaguang Liu; Peiqing Hu; Bi Zhu; Shujie Song; Marisol Fernández Ortiz; Yuji Ikeno; et al. (Advanced Science)
Abstract Oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) are key bioenergetics pathways. The machineries for both processes are localized in mitochondria. Secondary OXPHOS defects have been documented in patients with primary FAO deficiencies, and vice versa. However, the underlying mechanisms remain unclear. Intrigued by the observations that regulation of supercomplexes (SCs) assembly in a mouse OXPHOS deficient cell line and its derivatives is associated with the changes in lipid metabolism, a proteomics analysis is carried out and identified mitochondrial trifunctional protein (MTP) subunit alpha (hydroxyacyl‐CoA dehydrogenase trifunctional multienzyme complex subunit alpha, HADHA) as a potential regulatory factor for SCs assembly. HADHA‐Knockdown cells and mouse embryonic fibroblasts (MEFs) derived from HADHA‐Knockout mice displayed both reduced SCs assembly and defective OXPHOS. Stimulation of OXPHOS induced in cell culture by replacing glucose with galactose and of lipid metabolism in mice with a high‐fat diet (HFD) both exhibited increased HADHA expression. HADHA Heterozygous mice fed with HFD showed enhanced steatosis associated with a reduction of SCs assembly and OXPHOS function. The results indicate that HADHA participates in SCs assembly and couples FAO and OXPHOS.